1990
DOI: 10.1515/znb-1990-0916
|View full text |Cite
|
Sign up to set email alerts
|

A New Example of Edge-to-Face Interaction of Aromatic Rings in Oligopeptides: Cyclolinopeptide A

Abstract: The analysis of the aromatic region of 1H and 13C NMR spectra of cyclolinopeptide A (cyclic nonapeptide with the sequence c—(Pro— Pro— Phe—Phe—Leu— Ile— Ile— Leu— Val— ), (CLA)) shows that Phe-3 and Phe-4 aromatic rings are oriented nearly perpendicularly to each other, forming edge-to-face pair. It signifies the strong limitation of the free rotation of aromatic residues, probably because of the steric hindrance exerted by proximal aliphatic side chains of CLA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1992
1992
2006
2006

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 4 publications
(4 reference statements)
0
1
0
Order By: Relevance
“…An interesting feature of the CLA conformation is the reciprocal orientation of the aromatic rings of the two Phe residues. The rings are perpendicular to each other, forming an edge-to-face interaction [25]. The experiments with tyrosine analogues of CLA unequivocally showed that the residue in the position 4 plays a role of the 'edge' and the one in position 3 a role of the 'face' in this interaction.…”
Section: Structurementioning
confidence: 94%
“…An interesting feature of the CLA conformation is the reciprocal orientation of the aromatic rings of the two Phe residues. The rings are perpendicular to each other, forming an edge-to-face interaction [25]. The experiments with tyrosine analogues of CLA unequivocally showed that the residue in the position 4 plays a role of the 'edge' and the one in position 3 a role of the 'face' in this interaction.…”
Section: Structurementioning
confidence: 94%